Age estimation and growth patterns in young harbor seals (Phoca vitulina vitulina) during rehabilitation - Rapado-Tamarit, Beatriz; Méndez-Aróstegui, Margarita; de Reus, Koen; Sarraude, Tom; Pen, Ido; Groothuis, Ton G. G. (OXFORD UNIV PRESS INC, 2025)
To study patterns in behavior, fitness, and population dynamics, estimating the age of the individuals is often a necessity. Specifically, age estimation of young animals is very important for animal rehabilitation centers because it may determine if the animal should be taken in and, if so, what care is optimal for its rehabilitation. Accurate age estimation is also important to determine the growth pattern of an individual, and it is needed to correctly interpret the influence of early body condition on its growth trajectories. The purpose of our study was to find body measurements that function as good age estimators in young (up to 3 months old) harbor seals (Phoca vitulina vitulina), placing emphasis on noninvasive techniques that can be used in the field. To meet this goal, body mass (BM), dorsal standard length (DSL), upper canine length (CL), body condition (BC), and sex were determined from 45 Harbor Seal pups of known age. Generalized additive mixed models were fitted to find how well these morphometric measures predicted age, and the results from the selected model were used to compute growth curves and to create a practical table to determine the age of young animals in the field. We found that both DSL and CL-and to some extent sex-were useful predictors for estimating age in young harbor seals and that the growth rate of pups raised in captivity is significantly lower than for those raised in the wild. In addition, we found no evidence for compensatory growth, given that animals that arrived at the center with a poor BM or BC continued to show lower BM or BC throughout almost the entire rehabilitation period.Study on young harbor seals reveals that body measurements such as body and teeth length can accurately estimate their age, aiding in conservation and rehabilitation efforts. Captive-raised pups grow differently from those in the wild, and initial poor body condition persists during rehabilitation.Para estudiar patrones de comportamiento, eficacia biol & oacute;gica y din & aacute;mica poblacional, a menudo es necesario estimar la edad de los individuos. Espec & iacute;ficamente, la estimaci & oacute;n de la edad de animales j & oacute;venes es muy importante para los centros de rehabilitaci & oacute;n, ya que puede determinar si el animal joven debe ser ingresado y, en caso afirmativo, qu & eacute; cuidados espec & iacute;ficos ser & iacute;an los & oacute;ptimos para su rehabilitaci & oacute;n. La estimaci & oacute;n precisa de la edad tambi & eacute;n es importante para determinar el patr & oacute;n de crecimiento de un individuo, y es necesaria para interpretar correctamente la influencia de la condici & oacute;n corporal temprana en sus trayectorias de crecimiento. El prop & oacute;sito de nuestro estudio era encontrar medidas corporales que funcionen como buenos estimadores de edad en focas comunes j & oacute;venes (de hasta 3 meses de edad; Phoca vitulina vitulina), poniendo & eacute;nfasis en t & eacute;cnicas no invasivas que puedan usarse en el campo. Para alcanzar este objetivo, se ha medido la masa corporal (BM), la longitud dorsal est & aacute;ndar (DSL), la longitud del canino superior (CL), la condici & oacute;n corporal (BC) y el sexo de 45 cr & iacute;as de foca com & uacute;n de edad conocida. Se ha aplicado modelado estad & iacute;stico para determinar la eficacia de las medidas morfom & eacute;tricas para predecir la edad, y los resultados del modelo seleccionado se han usado para calcular las curvas de crecimiento y crear una tabla pr & aacute;ctica para usar en el campo. Descubrimos, por un lado, que tanto DSL como CL, y hasta cierto punto el sexo, parecen ser predictores importantes para estimar la edad en focas comunes j & oacute;venes, y, por otro, que la tasa de crecimiento de las cr & iacute;as alimentadas en cautividad es significativamente menor que la de las criadas en la naturaleza. Adem & aacute;s, no encontramos evidencia de crecimiento compensatorio, dado que los animales que llegaron al centro con una mala masa o condici & oacute;n corporal continuaron mostrando una masa o condici & oacute;n corporal m & aacute;s baja durante casi todo el per & iacute;odo de rehabilitaci & oacute;n.